2013
DOI: 10.3109/15412555.2013.829436
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiopoietin-2 and CRP Levels During COPD Exacerbations

Abstract: Available online on: 15.01.2018@http://ijrdpl.co m http://dx. ABSTRACT: Background: Chronic Obstructive pulmonary disease a systemic inflammatory disease, characterized by airway inflammation and progressive airflow limitation is an increasing cause of morbidity and mortality worldwide including India. C-reactive protein (CRP) is an acute phase reactant secreted by the liver in response to infection, inflammation or tissue damage. Objectives: The aim of this study was to investigate serum levels of CRP in Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…As opposed to the subjective and variable physical and physiological endpoints used to guide therapy in stable COPD, there are no reliable indicators of a patient's exacerbation status, susceptibility, or disease progression. Accordingly, there is a growing interest in the development and use of biomarkers to assess disease and predict disease progression in COPD [26][27][28][29] . Ideally, biomarkers will better reflect disease activity while representing biologically relevant pathways.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…As opposed to the subjective and variable physical and physiological endpoints used to guide therapy in stable COPD, there are no reliable indicators of a patient's exacerbation status, susceptibility, or disease progression. Accordingly, there is a growing interest in the development and use of biomarkers to assess disease and predict disease progression in COPD [26][27][28][29] . Ideally, biomarkers will better reflect disease activity while representing biologically relevant pathways.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…The levels of Ang-2 decreased after a week of treatment. Patients with poorer outcomes also had significantly higher Ang-2 levels [118]. This suggests that Ang-2 might be a useful biomarker for COPD exacerbations and might help clinicians identify patients at risk of worse outcomes at the start of an exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…CRP levels were found to be elevated among the smokers than the non-smokers. A similar study showed a decrease in serum CRP levels based on a week of hospitalization in COPD patients [ 50 ].…”
Section: Discussionmentioning
confidence: 91%